Aktivitas Antioksidan Dan Kualitas Organoleptik Yogurt Susu Kambing Etawa Dengan Sari Buah Bit (Beta vulgaris L.) - Beni Pratama Setiawan; Jeki Mediantari Wahyu Wibawanti; Hanung Dhidhik Arifin (Universitas Muhammadiyah Purworejo, 2019)
The study aims to determine the effect of the addition of beet juice concentration according to the treatment of antioxidant activity and organoleptic quality of etawa goat milk yogurt. The process of research and organoleptic testing was carried out at the Integrated Laboratory of Muhammadiyah University Purworejo and the antioxidant activity test at a private laboratory in Yogyakarta. The material used was 5 liters of etawa goat milk, 1/2 liter beet juice and bacteria Lactobacillus bulgaricus and Streptococcus thermopilus, samples were taken of 125 plastic containers with a contents of 25 ml/sample for organoleptic tests and 20 bottles with 30 ml contents/sample for antioxidant activity test. The treatments given were S0 (0%), S5 (5%), S10 (10%), S15 (15%) and S20 (20%). The method used was a completely randomized design (CRD) with 5 treatments and 4 replications. Parameters measured were antioxidant activity and organoleptic quality (color, aroma, taste, and texture). The results showed the treatment of the concentration of the addition of beet juice was significantly different (P <0.05) on the antioxidant activity and color of yogurt but not significantly different (P> 0.05) on the aroma, taste, and texture of yogurt. The results of antioxidant activity were 17.00, 27.25, 36.17, 40.34, and 45.01. Yogurt color values ​​of 1.48, 3.16, 3.04, 4.08 and 4.60. The value of yogurt aroma is 2.40, 2.72, 2.64, 2.68 and 3.08. The value of yogurt is 1.96, 1.72, 1.88, 2.40, and 2.48. Yogurt texture values ​​of 2.68, 2.84, 3.36, 3.28 and 3.60. Beet juice can increase the value of the antioxidant activity and organoleptic quality between treatments but not too significantly (P> 0.05) on the results of organoleptic tests on the aroma, taste, and texture parameters. Further beetroot research needs to be done.